ANALISIS KAPASITAS RUANG PARKIR PADA RSUD BANYUMAS - DWI SRI WIYANTI (Fakultas Teknik Universitas Wijayakusuma Purwokerto, 2014)
Parking is one of the important elements of hospital. The increase of activitiesparticularly hospital in RSUD Banyumas, requires sufficient supply of parking facility.However, so far there is no study on parking characteristics and quantification of standardparking spaces demand. The objectives of this study are to analyse capacity spaces parkingand to analyse standard of parking spaces demand. Data required are primary data which isobtained from survey on site toobtain parking characteristics. Primary data were obtainedfrom seven day survey an Monday - Saturday between 06.30 am to 21.30 pm and secondarydata is obtained from the management which is used to analyse standard parking spacedemand.Pursuant to result analyse, is hence got by result sum up the check park needed at themoment pursuant to accumulation culminate is to motorbike needed 614 SRP, for car needed193 SRP.From the analysis highest parking index capacity spaces parking hospital in RSUDBanyumas, with parking supply problems. The solutions to be obtained parking spacedemand of parking facility like special parking building area for parking supplayKeywords: capacity, characteristics, parking, hospital